Association of pretransplant kidney function with outcomes after lung transplantation. Issue 5 (4th April 2017) - Banga, Amit; Mohanka, Manish; Mullins, Jessica; Bollineni, Srinivas; Kaza, Vaidehi; Torres, Fernando; Tanriover, Bekir
Abstract: Purpose: There is a lack of data regarding the independent association of pretransplant kidney function with early and late outcomes among lung transplant (LT) recipients. Methods: We queried the United Network for Organ Sharing database for adult patients (≥18 years of age) undergoing LT between 1987 and 2013. Glomerular filtration rate (GFR) was estimated using the modification of diet in renal disease (MDRD) and the Chronic kidney disease epidemiology collaboration (CKD‐EPI) equations. The study population was split into four groups (>90, 60‐90, 45‐59.9, and <45 mL/min/1.73 m 2 ) based on the estimated GFR at the time of listing. Results: Overall, there was a good correlation between the GFR estimated from the two equations (n=17884, Pearson r =.816, P <.001). There was a consistent and independent association of worse early and late outcomes with declining GFR throughout the spectrum including those above 60 mL/min/1.73 m 2 ( P <.001 for overall comparisons). Although GFR<45 mL/min/1.73 m 2 was associated with worse early and late survival, patients with GFR 45‐59.9 mL/min/1.73 m 2 do not appear to have survival advantage beyond 3 years post‐transplant. Conclusion: There is a good correlation between GFR estimated using MDRD and CKD‐EPI equations among patients being considered for LT. Early and late outcomes after LT worsen in a linear fashion with progressively lower pretransplant GFR.